Modern Information Technologies in Medicine - Sayfullayev Ramziddin Fazliddinovich; Uroqova Ma’mura G‘olibjon qizi; Sanaqulova Marjona Jaxongir qizi; Yuldasheva Zaynab Abdug‘ani qizi; Tilovov Umidjon Bekzod o’g’li (Researchparks Publishing, 2023)
The subjects (courses) of